2020
DOI: 10.1039/c9ra08042b
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of α-terpineol by Alternaria alternata

Abstract: a-Terpineol (1), the main volatile constituent in some traditional Chinese medicines, has been reported to be metabolized to 4R-oleuropeic acid by the larvae of common cutworms. The present study verified that a-terpineol could be converted to 4R-oleuropeic acid (2) and (1S,2R,4R)-p-menthane-1,2,8-triol (3) by Alternaria alternata fermentation. Using shortened fermentation times, 7-hydroxy-a-terpineol (2a) was identified as an oxidative intermediate, which was consistent with the hypothesis put forward by prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…This mixture was subjected to a transesterification reaction with K 2 CO 3 in methanol. This afforded previously reported monoterpenoid 7 c [29] (Figure 5) and a mixture of two fatty acid methyl esters. GC-MS analysis revealed two peaks with masses m/z 354 ( The NMR spectroscopic, MS and optical rotation data associated with monoterpene 7 c were in agreement with equivalent data reported for this compound {lit.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…This mixture was subjected to a transesterification reaction with K 2 CO 3 in methanol. This afforded previously reported monoterpenoid 7 c [29] (Figure 5) and a mixture of two fatty acid methyl esters. GC-MS analysis revealed two peaks with masses m/z 354 ( The NMR spectroscopic, MS and optical rotation data associated with monoterpene 7 c were in agreement with equivalent data reported for this compound {lit.…”
Section: Resultsmentioning
confidence: 56%
“…GC-MS analysis revealed two peaks with masses m/z 354 ( The NMR spectroscopic, MS and optical rotation data associated with monoterpene 7 c were in agreement with equivalent data reported for this compound {lit. [29] [α] D 25 À 25.1 (c 0.020, CHCl 3 )}. [29,30] Unusual terpene wax esters 4 a and 4 b represent first in class monoterpenoid wax esters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Our previous studies have shown that microbial autogenic metabolic processes and many transformations have been achieved by microorganisms. 6 11 …”
Section: Introductionmentioning
confidence: 99%
“…Biotransformation shows great advantages compared with chemical synthesis due to its regio- and stereoselectivity, environmentally friendly procedures, and mild reaction conditions. , In general, biotransformations can replace a multistep synthesis with a single microbial transformation. , Therefore, bioconversion could play a critical role in the synthesis of bioactive compounds . Our previous studies have shown that microbial autogenic metabolic processes and many transformations have been achieved by microorganisms. …”
Section: Introductionmentioning
confidence: 99%